PENGEMBANGAN TES DIAGNOSTIK TWO TIER MULTIPLE CHOICE PADA MATERI METABOLISME SEL SEKOLAH MENENGAH PERTAMA - Wulansari, Tia; Mardiyyaningsih, Asriah Nurdini; Yeni, Laili Fitri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Errors and limitations in constructing knowledge cause students to experience misconceptions. Potential misconceptions can be identified at the beginning of learning using diagnostic tests. Cell metabolism material for junior high school students is one of the materials that has the potential for misconceptions. The concepts contained in this material are not only accepted at the junior high school level but will continue to be studied until the next level of education, so it is necessary to ensure that students do not experience misconceptions. This study aims to describe the process of developing a two tier multiple choice diagnostic test on cell metabolism material in class VII junior high school. This test was developed using Thiagarajan's 4D method with a modification of Tessmer's stages. Test feasibility assessment includes content validation and empirical validation. Content validation by three experts and empirical validation with 30 students. The results showed that all questions were feasible to use and had a point biserial correlation value greater than the r table value of 0.369 to 0.587 and a reliability of 0.781. So, it can be concluded that the two tier multiple choice diagnostic test developed is feasible to use to diagnose student misconceptions on cell metabolism material.